Entrepreneurial Intentions of Science, Technology, Engineering and Mathematics Students at the University of Witwatersrand, Johannesburg, South Africa - Mazibuko, Ntathu (University of the Witwatersrand, Johannesburg, 2023)
Entrepreneurship is one of the solutions put forward to curb the rising unemployment statistics in South Africa. It is argued that Entrepreneurial Intentions are a good indicator of Entrepreneurial Activity. The study examines the relationship and influence of Entrepreneurial Self-Efficacy together with Innovation and Entrepreneurial Education on Entrepreneurial Intentions. The subject of this study involved students from the University of Witwatersrand, Faculty of Engineering and Built Environment who are studying Science, Technology, Engineering and Mathematics (STEM) courses. The study collected data from a random sample of 60 students using an adapted questionnaire. The descriptive as well as inferential statistics were used to analyse the data. The results show Entrepreneurial Education does not have significant impact on the students’ Entrepreneurial Intentions, whilst Entrepreneurial Self-Efficacy and Innovation showed a positive relationship. Results also showed that high Entrepreneurial Intentions do not translate to Entrepreneurial Activity.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Entrepreneurial intention; entrepreneurship; SDG-9: Industry, innovation and infrastructure